Epidemiology of the Cnidarian Physalia physalis stings attended at a health care center in beaches of Adicora, Venezuela - Cazorla-Perfetti, Dalmiro J.; Loyo, Jesus; Lugo, Lusneida; Acosta, Maria E.; Morales, Pedro; Haddad, Vidal [UNESP]; Rodriguez-Morales, Alfonso J. (Elsevier B.V., 2012)
Stings caused by jellyfish and jellyfish-like colonies are common all around the world, with serious manifestations and occasional deaths reported in some countries. Between December 2006 and 2007, epidemiological, clinical and treatment aspects of stings caused by the Portuguese man-of-war (Physalia physalis) in 59 patients consulting the ambulatory emergency in Adicora, Falcon State, Venezuela, were studied. Most of the stings occurred in males (59%) preschool and school-aged children (49%), visitors from other areas of the country (92%) during holidays when bathing or diving at the beach (97%). Injuries presented linear erythematous plaques at the point of contact with the animal, located in several anatomical sites. Most clinical manifestations observed were: intense burning pain, urticaria, erythema and inflammation (100%), as well dyspnea with laryngeal edema and fever (19%). Patients were treated with topical drugs, including antihistamine and antipyretic drugs, but also with systemic hydrocortisone. P. physalis stings in Adicora appeared to have a seasonal pattern, with systemic complications potentially life-threatening. Thus, epidemiological surveillance program is recommended, particularly in travelers. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Physalia; Travel; Stings; Beaches; Venezuela